Preparation method of tourmaline / zeolite composite material and application of tourmaline / zeolite composite material in removal of reducing toxic ions in water
By preparing and modifying tourmaline/zeolite composite materials, the complexity and high cost problems of removing toxic ions such as trivalent arsenic in water in the prior art are solved, and efficient and economical water removal effect is achieved, and the reuse of materials is supported.
Patent Information
- Application Number
- CN202510132792.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art has problems such as complex operation, high cost or secondary pollution when removing reducing toxic ions such as trivalent arsenic in water, and research on tourmaline/zeolite composites in this field has not yet been thorough.
By preparing tourmaline/zeolite composites, the specific steps include cleaning, drying, crushing, grinding, mixing, stirring, filtration and calcining to form a composite material with high adsorption capacity, and enhance its adsorption performance through modification treatment.
The composite material effectively removes reducing toxic ions in water at a wide range of pH values, and can be regenerated by rinsing deionized water after adsorption, realizing reuse of materials and reducing treatment costs.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a method for preparing tourmaline / zeolite composite material and its application in removing reducing toxic ions from water. Background Technology
[0002] With the acceleration of industrialization, water pollution has become increasingly severe, especially the increased emissions of heavy metal pollutants such as arsenic, which have placed enormous pressure on the ecological environment. Arsenic is a highly toxic element, and long-term exposure to high concentrations of arsenic can pose serious threats to human health, including but not limited to skin lesions, cardiovascular diseases, and cancer. It is worth noting that trivalent arsenic (As(III)) is far more toxic than pentavalent arsenic (As(V)). Therefore, in treating arsenic-containing wastewater, it is usually necessary to first oxidize As(III) to As(V) before removal. Thus, developing efficient arsenic removal technologies has become a research hotspot in the environmental protection field.
[0003] Traditional arsenic removal methods mainly include chemical precipitation, ion exchange, and membrane separation, but these methods often suffer from problems such as complex operation, high cost, or secondary pollution. In recent years, natural minerals have gained widespread attention as adsorbents due to their wide availability, low cost, and environmental friendliness. Tourmaline, a boron-containing silicate mineral, not only possesses excellent electrical properties but also exhibits certain adsorption performance; while zeolite is known for its unique pore structure and high ion exchange capacity. Theoretically, combining these two minerals can combine their respective advantages, thereby enhancing the adsorption effect on arsenic.
[0004] However, current research on tourmaline / zeolite composite materials is still in its early stages, particularly lacking systematic studies on the effective removal of specific pollutants such as trivalent arsenic. Therefore, exploring a simple, cost-effective, and efficient preparation process for tourmaline / zeolite composite materials is of great significance for improving water quality and promoting sustainable development. This invention is proposed based on this need. Summary of the Invention
[0005] One object of the present invention is to solve at least the above-mentioned problems and / or defects, and to provide at least the advantages described below.
[0006] To achieve these objectives and other advantages according to the present invention, a method for preparing a tourmaline / zeolite composite material is provided, comprising the following steps:
[0007] Step 1: The artificial zeolite and natural tourmaline are washed, dried, crushed, ground, and sieved to obtain zeolite powder and tourmaline powder, respectively.
[0008] Step 2: Mix zeolite powder and tourmaline powder in a certain proportion, add water and mix evenly with a mixer to obtain a mixed slurry. Filter the mixed slurry and dry it.
[0009] Step 3: Calcine the dried object to obtain tourmaline / zeolite composite material.
[0010] Preferably, in step one, the artificial zeolite is composed of Na. 96 Al 96 Si 96 O 384 When sieving zeolite powder, pass it through a 300-mesh sieve.
[0011] Preferably, in step one, the natural tourmaline is composed of Na. 0.8 Mg3Al6B3O9Si6O 18 (OH)4, tourmaline powder should be sieved through a 300-mesh sieve.
[0012] Preferably, in step two, the mass ratio of zeolite powder, tourmaline powder, and water is 1-3:1-4:3-4.
[0013] Preferably, in step two, when stirring the zeolite powder and tourmaline powder, a mechanical mixer is used to stir at a speed of 100-300 rpm for 18-24 hours.
[0014] Preferably, in step two, the drying temperature is 80–100°C and the drying time is 8–12 hours.
[0015] Preferably, in step two, the filtration method is centrifugal filtration, where the supernatant is removed after centrifugation at a speed of 8000-12000 r / min for 5-10 min.
[0016] Preferably, in step three, the calcination conditions are calcination at 600–800°C for 4–5 hours in a muffle furnace.
[0017] An application of a tourmaline / zeolite composite material, wherein the tourmaline / zeolite composite material is used to remove reducing toxic ions from water.
[0018] Preferably, the tourmaline / zeolite composite material is used to remove trivalent arsenic ions from water.
[0019] Preferably, after obtaining the tourmaline / zeolite composite material in step three, it is modified. The modification method is as follows:
[0020] S1. Add NaOH solution to FeCl3 solution and stir for 1-4 hours to mix evenly. Then age at room temperature for 1-7 days to obtain ferric hydroxide solution.
[0021] S2. Grind the tourmaline / zeolite composite material into powder, then add it to the iron hydroxide solution, control the solid-liquid ratio of the powder and the solution, stir the mixture until it becomes viscous, then flash dry the mixture, and finally calcine it to obtain the modified tourmaline / zeolite composite material.
[0022] Preferably, in S1, the concentration of NaOH solution is 0.1–1 mol / L, the concentration of FeCl3 solution is 0.2–1 mol / L, and the volume ratio of NaOH solution to FeCl3 solution is 2–8:1.
[0023] Preferably, in step S2, the solid-liquid ratio of the tourmaline / zeolite composite powder to the ferric hydroxide solution is 1:0.1 to 0.5, the flash drying temperature is 200 to 300°C, the calcination temperature is 600 to 700°C, and the calcination time is 3 to 6 hours.
[0024] The present invention has at least the following beneficial effects:
[0025] (1) The tourmaline / zeolite composite material of the present invention, when treating reducing toxic ions in water, exhibits good performance over a wide pH range of 3.0 to 11.0, and also effectively reduces chloride ions (Cl... - ), sulfate ions (SO4) 2- Sodium ions (Na) + ), calcium ions (Ca 2+ ), magnesium ions (Mg 2+ Even when competing substances such as organic acids coexist, it can still effectively reduce the content of reducing toxic ions in water.
[0026] (2) The tourmaline / zeolite composite material of the present invention has a strong adsorption capacity for reducing toxic ions. After adsorption saturation, it can be regenerated by rinsing with deionized water, thereby realizing the reuse of the material and greatly reducing the processing cost. This makes the composite material more economical and practical in practical applications.
[0027] (3) The tourmaline / zeolite composite material of the present invention effectively overcomes the technical bottlenecks of traditional adsorption materials in practical engineering applications through reasonable physical and chemical modification. The composite material has good structural stability and mechanical strength, can adapt to various complex water treatment environments, and ensures reliability and durability in practical engineering.
[0028] (4) The present invention also modifies the tourmaline / zeolite composite material by introducing hydroxyl iron to increase the number of hydroxyl groups on the surface of the composite material, so that it can combine more with reducing toxic ions in water, and then combine with hydroxyl iron ion solution to form a polymer, thereby enhancing the adsorption capacity. At the same time, due to the effect of hydroxyl iron ions, it can complex with reducing toxic ions in water at a deeper level, which greatly enhances the adsorption performance of reducing toxic ions in wastewater.
[0029] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Detailed Implementation
[0030] The present invention will now be described in further detail so that those skilled in the art can implement it based on the description.
[0031] Example 1
[0032] A method for preparing a tourmaline / zeolite composite material includes the following steps:
[0033] Step 1: The artificial zeolite and natural tourmaline are washed, dried, crushed, ground, and sieved through a 300-mesh sieve to obtain zeolite powder and tourmaline powder, respectively.
[0034] Step 2: Mix 300g of zeolite powder and 200g of tourmaline powder in the specified ratio, add 300mL of water, and then put the mixture into a mixer and stir at 100rpm for 24h. After mixing evenly, a slurry is obtained. Centrifuge the slurry at 8000r / min for 5min, filter to remove the supernatant, and dry it at 80℃ for 12h using a drying device.
[0035] Step 3: Place the dried object into a muffle furnace and calcine it at 600℃ for 5 hours to obtain tourmaline / zeolite composite material.
[0036] The prepared tourmaline / zeolite composite material was applied to the removal of trivalent arsenic ions from water, including:
[0037] 50 mg of tourmaline / zeolite composite material was added to 100 mL of water containing trivalent arsenic ions (arsenic ion concentration of 5 mg / L), and the pH was adjusted to 9. The adsorption experiment was then conducted for 5 hours at 25°C and 250 rpm in a constant-temperature shaker. After shaking, the solution was filtered, and the supernatant was analyzed. The trivalent arsenic ions in the solution were converted to pentavalent arsenic ions, which are less toxic. The concentration of trivalent arsenic ions decreased to 0.005 mg / L, and the concentration of pentavalent arsenic ions decreased to below 0.01 mg / L. The filtered composite material was then washed with deionized water and recycled, achieving a reuse rate of 90%.
[0038] Example 2
[0039] Tourmaline / zeolite composite materials were prepared using the same method as in Example 1, and applied to the removal of reducing toxic ions from water. The pH of the aqueous solution was adjusted to 9, with the difference being that the toxic substance in the water was methylmercury (concentration of 5 mg / L). The experimental results showed that the methylmercury in the solution was converted into the less toxic divalent mercury ions, with the methylmercury concentration decreasing to 0.007 mg / L and the divalent mercury ion concentration decreasing to below 0.01 mg / L.
[0040] Example 3
[0041] Tourmaline / zeolite composite materials were prepared using the same method as in Example 1, and used to remove reducing toxic ions from water. The pH of the aqueous solution was adjusted to 9. The difference was that the toxic substance in the water was adjusted to tetravalent selenide ions (concentration of 5 mg / L). The experimental results showed that the tetravalent selenide ions in the solution were converted into the less toxic hexavalent selenide ions, with the tetravalent selenide ion concentration decreasing to 0.005 mg / L and the hexavalent selenide ion concentration decreasing to below 0.01 mg / L.
[0042] Example 4
[0043] Tourmaline / zeolite composite materials were prepared using the same method as in Example 1, and were used to remove reducing toxic ions from water. The difference was that the pH of the water was adjusted to 3, and the toxic substance in the water was trivalent arsenic (concentration of 5 mg / L). The experimental results showed that the trivalent arsenic in the solution was converted into the less toxic pentavalent arsenic, with the trivalent arsenic ion concentration decreasing to 0.06 mg / L and the pentavalent arsenic concentration decreasing to below 0.08 mg / L.
[0044] Example 5
[0045] Tourmaline / zeolite composite materials were prepared using the same method as in Example 1, and were used to remove reducing toxic ions from water. The difference was that the pH of the water was adjusted to 5, and the toxic substance in the water was trivalent arsenic (concentration of 5 mg / L). The experimental results showed that the trivalent arsenic in the solution was converted into the less toxic pentavalent arsenic, with the trivalent arsenic ion concentration decreasing to 0.04 mg / L and the pentavalent arsenic ion concentration decreasing to below 0.03 mg / L.
[0046] Example 6
[0047] Tourmaline / zeolite composite materials were prepared using the same method as in Example 1, and used to remove reducing toxic ions from water. The difference was that the pH of the water was adjusted to 7, and the toxic substance in the water was trivalent arsenic (concentration of 5 mg / L). The experimental results showed that the trivalent arsenic in the solution was converted into pentavalent arsenic ions, which are less toxic. The concentration of trivalent arsenic ions decreased to 0.008 mg / L, and the concentration of pentavalent arsenic ions decreased to below 0.01 mg / L.
[0048] Example 7
[0049] Tourmaline / zeolite composite materials were prepared using the same method as in Example 1, and were used to remove reducing toxic ions from water. The difference was that the pH of the water was adjusted to 11, and the toxic substance in the water was trivalent arsenic (concentration of 5 mg / L). The experimental results showed that the trivalent arsenic in the solution was converted into pentavalent arsenic ions, which are less toxic. The concentration of trivalent arsenic ions decreased to 0.005 mg / L, and the concentration of pentavalent arsenic ions decreased to below 0.007 mg / L.
[0050] Example 8
[0051] Tourmaline / zeolite composite materials were prepared using the same method as in Example 1, and were used to remove reducing toxic ions from water. The difference was that the pH of the water was adjusted to 9, and the interfering ion in the water was set as sulfate ions (concentration of 5 mg / L), and the toxic substance in the water was set as trivalent arsenic (concentration of 5 mg / L). The experimental results were as follows: the trivalent arsenic in the solution was converted into the less toxic pentavalent arsenic ions, the concentration of trivalent arsenic ions decreased to 0.005 mg / L, and the concentration of pentavalent arsenic ions decreased to below 0.008 mg / L; the concentration of sulfate ions in the solution was 4.785 mg / L.
[0052] Example 9
[0053] In this embodiment, the tourmaline / zeolite composite material obtained in Example 1 is modified. The modification method is as follows:
[0054] S1. Add 3L of 0.15mol / L NaOH solution to 1L of 0.1mol / L FeCl3 solution and stir for 2.5h to mix evenly. Then age at room temperature for 3 days to obtain ferric hydroxide solution.
[0055] S2. Grind the tourmaline / zeolite composite material into powder, then add it to the iron hydroxide solution, control the solid-liquid ratio of powder to solution to be 1:0.5, stir the mixture until it becomes viscous, then flash dry the mixture at 200℃, and calcine it at 650℃ for 4 hours after drying to obtain the modified tourmaline / zeolite composite material.
[0056] 50 mg of modified tourmaline / zeolite composite material was added to 100 mL of water containing trivalent arsenic ions (arsenic ion concentration of 5 mg / L), and the pH was adjusted to 9. Then, an adsorption experiment was carried out in a constant temperature shaker at 250 r / min and 25 °C for 5 hours. After shaking, the solution was filtered, and the supernatant was analyzed. The trivalent arsenic ions in the solution were converted into pentavalent arsenic ions with lower toxicity. The concentration of trivalent arsenic ions decreased to 0.002 mg / L, and the concentration of pentavalent arsenic ions decreased to below 0.005 mg / L.
[0057] This embodiment modifies the tourmaline / zeolite composite material by introducing ferric hydroxide, increasing the number of hydroxyl groups on the surface of the composite material. This allows it to combine more with reducing toxic ions in water. Then, it is compounded with ferric hydroxide ion solution to form a polymer, which enhances the adsorption capacity. At the same time, due to the effect of ferric hydroxide ions, it can complex with reducing toxic ions in water at a deeper level, which greatly enhances the adsorption performance of reducing toxic ions in wastewater.
[0058] Comparative Example 1
[0059] In this comparative example, artificial zeolite was used as the adsorbent alone. The artificial zeolite was washed with deionized water, dried in a dryer, crushed and ground, and then passed through a 300-mesh sieve to obtain zeolite powder.
[0060] 50 mg of zeolite powder was added to 100 mL of water containing trivalent arsenic ions (arsenic ion concentration of 5 mg / L), and the pH was adjusted to 9. The adsorption experiment was then conducted for 5 hours at 25°C and 250 rpm in a constant-temperature shaker. After shaking, the solution was filtered, and the supernatant was analyzed. The trivalent arsenic ions in the solution were converted into the less toxic pentavalent arsenic ions, with the trivalent arsenic ion concentration decreasing to 2.51 mg / L and the pentavalent arsenic ion concentration decreasing to below 0.54 mg / L. This comparative example only used artificial zeolite as the adsorbent, and its adsorption effect was limited, resulting in incomplete removal of trivalent arsenic ions from the water.
[0061] Comparative Example 2
[0062] In this comparative example, tourmaline alone was used as an adsorbent. Natural tourmaline was washed with deionized water, dried in a dryer, crushed and ground, and then passed through a 300-mesh sieve to obtain tourmaline powder.
[0063] 50 mg of tourmaline powder was added to 100 mL of water containing trivalent arsenic ions (arsenic ion concentration of 5 mg / L), and the pH was adjusted to 9. The adsorption experiment was then conducted for 5 hours at 25°C and 250 rpm in a constant-temperature shaker. After shaking, the solution was filtered, and the supernatant was analyzed. The trivalent arsenic ions in the solution were converted into the less toxic pentavalent arsenic ions, with the trivalent arsenic ion concentration decreasing to 1.44 mg / L and the pentavalent arsenic ion concentration decreasing to below 3.25 mg / L. This comparative example only used natural tourmaline as an adsorbent, which has limited adsorption effect and incomplete removal of trivalent arsenic ions from the water, resulting in a relatively high residual concentration of pentavalent arsenic ions in the water.
[0064] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details.
Claims
1. A method for preparing a tourmaline / zeolite composite material, characterized in that: The following steps are involved: Step 1, washing, drying, crushing, grinding and sieving artificial zeolite and natural tourmaline to obtain zeolite powder and tourmaline powder; Step 2: Mix zeolite powder and tourmaline powder according to a certain proportion, add water and mix them evenly with a stirrer to obtain a mixed slurry, and filter and dry the mixed slurry; Step 3: calcining the object obtained after drying to obtain a tourmaline / zeolite composite material.
2. The method for preparing the tourmaline / zeolite composite material according to claim 1, characterized in that: In the step 1, the composition of the artificial zeolite is Na 96 Al 96 Si 96 O 384 , zeolite powder passed through 300 mesh sieve.
3. The method for preparing the tourmaline / zeolite composite material according to claim 1, characterized in that: In the step 1, the composition of natural tourmaline is Na 0.8 Mg3Al6B3O9Si6O 18 (OH)4, tourmaline powder passed through 300 mesh sieve.
4. The method for preparing the tourmaline / zeolite composite material according to claim 1, characterized in that: In the step 2, the mass ratio of zeolite powder, tourmaline powder and water is 1-3:1-4:3-4.
5. The method for preparing the tourmaline / zeolite composite material according to claim 1, characterized in that: In the step 2, the zeolite powder and the tourmaline powder are stirred by a mechanical stirrer at a rotation speed of 100 to 300 rpm for 18 to 24 hours.
6. The method for preparing the tourmaline / zeolite composite material according to claim 1, characterized in that: In the step 2, the drying temperature is 80-100° C. and the drying time is 8-12 hours.
7. The method for preparing the tourmaline / zeolite composite material according to claim 1, characterized in that: In the step 2, the filtering method is centrifugal filtration, and after centrifuging for 5 to 10 minutes in a centrifuge at a rotation speed of 8000 to 12000 r / min, the supernatant is removed.
8. The method for preparing the tourmaline / zeolite composite material according to claim 1, characterized in that: In the step 3, the calcination condition is calcining at 600-800° C. for 4-5 hours in a muffle furnace.
9. An application of a tourmaline / zeolite composite material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The tourmaline / zeolite composite material is used to remove reducing toxic ions in water.
10. Use of the tourmaline / zeolite composite material according to claim 9, characterized in that: The tourmaline / zeolite composite material is applied to removing trivalent arsenic ions from water.
Citation Information
Cited By
Biomineralization contact oxidation reactor as well as preparation method and application thereof
CN120736673A